Immunogenicity of Type IV Pilin Proteins from Clostridium perfringens in Chickens - Audrey Charlebois; Nicolas Deslauriers; Lila Maduro; Martine Boulianne (Microorganisms)
Clostridium perfringens, the causative agent of necrotic enteritis in chickens, is controlled by in-feed antibiotics. With increasing pressure to reduce antimicrobial use, the development of alternative preventive tools is needed. Type IV pili proteins have been shown to be immunogenic in many Gram-positive bacteria. The aims of this study were to evaluate the immunogenic potential of pilins (PilA1, PilA2 and PilA3) from C. perfringens in chickens and to verify their ability to protect against necrotic enteritis. Chickens were immunized twice with 50 µg of recombinant proteins and adjuvant, resulting in a good and specific serum antibody response. Next, one-day-old chicks were injected three times with the same vaccines, and then infected with C. perfringens. Mean OD450 values ten times higher than the controls were obtained for IgY (p < 0.05) and a significantly lower cecal count of C. perfringens was observed in the birds injected with PilA3. However, no reduction in the severity of intestinal lesions was observed. All three pilin proteins were shown to be highly immunogenic in the chickens. Although immunization with the pilins did not protect the birds against necrotic enteritis in this study, it was interesting to observe that vaccination with the recombinant PilA3 protein reduced C. perfringens cecal colonization.